Involving Risk Reduction Practitioners and Other Experts in the Management of Super-Catastrophes via an Online Interactive Platform - Mignan, Arnaud; Mochel, Loïc; Ducos, Géraldine (Frontiers in Earth Science, 2022)
Super-catastrophes that lead to extensive disruption and loss amplification are frequently due to domino effects crossing natural, technological, and socio-economic systems. Although secondary effects of natural disasters are often considered in official hazard assessment platforms (e.g., landslides following earthquakes, storm surges), the main catalysts of long chains-of-events, which are network failure and business interruption, are generally not. This is partly due to the difficulty in handling complex and systemic situations. Yet in an increasingly interdependent world, crisis management requires foresight with the ability to consider those secondary effects. Such an ability can be brought in using interactive numerical tools. We have developed an online interactive platform for the pre-assessment phase of super-catastrophes based on Markov chain theory. The tool is centered on the elaboration of a transition matrix of event interactions, from which domino effects can be modeled and ranked in the background. Risk practitioners and other experts first list hazardous events, which are then populated in the matrix in both rows (trigger events) and columns (target events). As the square matrix grows, the platform’s users indicate which events can directly trigger another event in a binary approach. With enough participants, those binary decisions turn into weighted rules of interactions. In the process, the participants may discover missing links and update the matrix accordingly. To cover the full space of possibilities, three categories of events are systematically considered: natural, technological, and socio-economic. A group of experts can generate a transition matrix to explore the concept of super-catastrophe in general or to draw up possible crisis scenarios for decision-makers at any level of a territory (from a city to a country). Use of such a tool in practical situations, its integration into the management of prevention, planning for potential crisis situations, and training are discussed. Particular attention is given to the ability of this platform to help decision making within the context of a crisis unit with the need for quick evaluations.